Unmanned Aerial Vehicle (UAV) Photogrammetry for Heritage Building Documentation: Case Study Sasaksaat Train Station, Bandung, Indonesia - Wahyu Buana Putra; Gun Faisal; Nitih I. K. Dewi; Yohannes Firzal (International Journal of Environment, Architecture, and Societies, 2023)
Historic buildings are silent witnesses, bridging past, present, and future generations. The Sasaksaat Railway Station, which is inseparable from the 950-meter-long Sasaksaat Tunnel, is a treasure trove of historical heritage in West Java; it holds many stories and memories that are very closely related to the nation’s history, protected by Law Number 11 of 2010 concerning Cultural Heritage. This station is located in contoured land filled with dense vegetation, so a UAV photogrammetry method is needed in accordance with the character of the building and the area to be documented. The research documentation on these historical sites employs the UAV photogrammetry method, combining crosshatch flight plans, 60-degree tilt camera configurations, and making 3D BIM models using point cloud photogrammetry techniques. The research yielded impressive results, demonstrating the effectiveness of UAV Photogrammetry in accelerating the process of archiving historic buildings and their surroundings. The integration of this method significantly improves the documentation workflow, enabling comprehensive and detailed recording of the Sasak railway stations. This ANOVA test found no significant difference between manual size comparisons and photogrammetric results, even using direct geo-reference via UAV technology. The ease and reliability of this method approach can be recommended for low-cost historic building documentation activities.